2022
DOI: 10.3390/ijms231911467
|View full text |Cite
|
Sign up to set email alerts
|

ZnT2 Is Critical for TLR4-Mediated Cytokine Expression in Colonocytes and Modulates Mucosal Inflammation in Mice

Abstract: A wide range of microbial pathogens can enter the gastrointestinal tract, causing mucosal inflammation and infectious colitis and accounting for most cases of acute diarrhea. Severe cases of infectious colitis can persist for weeks, and if untreated, may lead to major complications and death. While the molecular pathogenesis of microbial infections is often well-characterized, host-associated epithelial factors that affect risk and severity of infectious colitis are less well-understood. The current study char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…In the small intestine, ZnT2 assumes a vital function in cytoplasmic zinc buffering, which is essential to Toll-like receptor 4 (TLR4) expression, initiation of pathogen-activated NF-κβ translocation, in addition to the release of cytokine in response to infectious challenges. 185 , 194 Furthermore, ZnT2 is indispensable for the development of lysosome biogenesis and bacterial-stimulated autophagy, 195 facilitating a powerful host defense and resolution machinery against enteric pathogens. In conclusion, this evidence suggests ZnT2 serves as an innovative modulator for mucosal inflammation in colonic cells and plays a crucial role in coping with infectious colitis, opening up possibilities on manipulating ZnT2 as a novel treatment strategy to particular intestinal infections.…”
Section: Role Of Cellular Zinc Metabolism Under Physiological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the small intestine, ZnT2 assumes a vital function in cytoplasmic zinc buffering, which is essential to Toll-like receptor 4 (TLR4) expression, initiation of pathogen-activated NF-κβ translocation, in addition to the release of cytokine in response to infectious challenges. 185 , 194 Furthermore, ZnT2 is indispensable for the development of lysosome biogenesis and bacterial-stimulated autophagy, 195 facilitating a powerful host defense and resolution machinery against enteric pathogens. In conclusion, this evidence suggests ZnT2 serves as an innovative modulator for mucosal inflammation in colonic cells and plays a crucial role in coping with infectious colitis, opening up possibilities on manipulating ZnT2 as a novel treatment strategy to particular intestinal infections.…”
Section: Role Of Cellular Zinc Metabolism Under Physiological Conditionsmentioning
confidence: 99%
“…In conclusion, this evidence suggests ZnT2 serves as an innovative modulator for mucosal inflammation in colonic cells and plays a crucial role in coping with infectious colitis, opening up possibilities on manipulating ZnT2 as a novel treatment strategy to particular intestinal infections. 194 ZIP8 is crucial for T cell activation, and recent studies have highlighted its significance in T cell function and innate immunity, which may have important implications in the context of inflammatory bowel disease (IBD). 145 , 196 In a study by Li et al, a novel association between Crohn’s disease (CD) and ZIP8 was identified.…”
Section: Role Of Cellular Zinc Metabolism Under Physiological Conditionsmentioning
confidence: 99%
“…Infants fed on maternal milk of ZnT2 gene-mutated mothers will occur serious zinc deficiency symptoms [5]. Moreover, recent research also shows that ZnT2 is related to gut dysbiosis and health in humans [6].…”
Section: Znt2mentioning
confidence: 99%
“…ZnT2 plays an important role in mammary epithelial cells (MECS) as a Zn importer, and ZnT2 defects in mice lead to reduced milk Zn concentrations, mammary gland function, and milk production [78]. In the context of infection, deletion of ZnT2 in mice with enteric Citrobacter rodentium infection leads to reduced proinflammatory responses compared to wildtype (WT) mice due to a reduction in the expression of Toll-like receptor 4 (TLR4) on colonocytes [79]. Interestingly, Zn itself is shown to play a direct role in the regulation of TLR4 expression, as modest Zn chelation using N,N,N′,N′,-tetrakis (2pyridylmethyl)ethylenediamine (TPEN), a Zn chelator, increased the expression of TLR4, suggesting ZnT2 attenuation leads to the accumulation of cytosolic Zn, thus loss of TLR4 expression [79].…”
Section: Solute-linked Carrier 30 (Znts)mentioning
confidence: 99%
“…In the context of infection, deletion of ZnT2 in mice with enteric Citrobacter rodentium infection leads to reduced proinflammatory responses compared to wildtype (WT) mice due to a reduction in the expression of Toll-like receptor 4 (TLR4) on colonocytes [79]. Interestingly, Zn itself is shown to play a direct role in the regulation of TLR4 expression, as modest Zn chelation using N,N,N′,N′,-tetrakis (2pyridylmethyl)ethylenediamine (TPEN), a Zn chelator, increased the expression of TLR4, suggesting ZnT2 attenuation leads to the accumulation of cytosolic Zn, thus loss of TLR4 expression [79]. ZnT3 is primarily localized in synaptic vesicles, and the release of Zn in presynaptic vesicles modulates neuronal transmission and plasticity [80,81].…”
Section: Solute-linked Carrier 30 (Znts)mentioning
confidence: 99%